Permainan Berbasis Alam sebagai Alternatif Mengurangi Ketergantungan Gadget pada Anak Usia Dini - Mukhlis Mukhlis; Lilyana Hasibuan (JURNAL TILA ( Tarbiyah Islamiyah Lil Athfaal ), 2026)
Excessive use of gadgets in early childhood can lead to dependency and impact children's physical and social development. This study aims to examine nature-based play as an alternative to reducing gadget dependency in early childhood. The study used a qualitative descriptive method with a literature review technique through various journals and relevant research from 2020 to 2025. The results show that nature-based play can increase children's physical activity, motor skills, creativity, and social interaction, and can help reduce screen time because children are more attracted to direct play activities in natural environments. Thus, nature-based play can be an effective alternative to reducing gadget dependency in early childhood. Keywords: nature-based play, gadget dependency, early childhood.